2005
DOI: 10.1161/01.cir.0000157151.10971.98
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Torsional Deformation by Doppler Tissue Imaging

Abstract: Background-Left ventricular (LV) torsional deformation is a sensitive index for LV performance but difficult to measure.The present study tested the accuracy of a novel method that uses Doppler tissue imaging (DTI) for quantifying LV torsion in humans with tagged magnetic resonance imaging (MRI) as a reference. Methods and Results-Twenty patients underwent DTI and tagged MRI studies. Images of the LV were acquired at apical and basal short-axis levels to assess LV torsion. We calculated LV rotation by integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(59 citation statements)
references
References 50 publications
4
53
1
1
Order By: Relevance
“…Tagged MRI has been considered the reference standard for noninvasive LVrot assessment. 8,18 However, MRI is of limited use because of lower temporal resolution and dissipation of tags during diastole. It is also time-consuming, technically demanding, and expensive.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tagged MRI has been considered the reference standard for noninvasive LVrot assessment. 8,18 However, MRI is of limited use because of lower temporal resolution and dissipation of tags during diastole. It is also time-consuming, technically demanding, and expensive.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
“…20 This was followed by attempts to decipher rotational mechanics using DTI. 18 However, the angle dependency of DTI remains a major limitation. 21,22 Two-dimensional STI, which is based on 2D tracking of unique speckle patterns created by the constructive and destructive interference of ultrasound beams within tissue, is independent of cardiac translation and angle dependency.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
“…Torsion can be measured by TDI and 2D speckle tracking, with both methods correlating with MRI 155 , 156 . Speckle tracking is the preferred technique given its angle independence and higher reproducibility; however, studies utilising this modality have demonstrated incongruent results.…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…The proper basal and apical levels were determined utilizing previously published criteria. 20 Offline analysis was performed on the digitally stored images using customized software on a personal computer workstation (EchoPAC; GE Vingmed, Noblesville, IN). All measurements of LV function and twist mechanics were made in a blinded fashion to exclude operator bias.…”
Section: Echocardiography Protocolmentioning
confidence: 99%